2013
DOI: 10.1073/pnas.1213871110
|View full text |Cite
|
Sign up to set email alerts
|

Shale gas development impacts on surface water quality in Pennsylvania

Abstract: Concern has been raised in the scientific literature about the environmental implications of extracting natural gas from deep shale formations, and published studies suggest that shale gas development may affect local groundwater quality. The potential for surface water quality degradation has been discussed in prior work, although no empirical analysis of this issue has been published. The potential for large-scale surface water quality degradation has affected regulatory approaches to shale gas development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
196
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(207 citation statements)
references
References 11 publications
6
196
0
5
Order By: Relevance
“…10 Ferrar et al (2013) 11 showed that treatment of wastewater by three of these facilities releases elevated concentrations of Cl, Br, Sr, and Ba to streams at concentrations above U.S. Environmental Protection Agency (USEPA) maximum contaminant levels, secondary maximum contaminant levels, criterion maximum concentrations, or criterion chronic concentrations. 11 The disposal of Marcellus wastewater through treatment facilities was also suggested to be linked to an overall increase of 5% in chloride concentrations at downstream surface water monitoring sites in western Pennsylvania 12 and likely increased the salt intake at downstream water treatment facilities. 6,13 Veil (2010) 10 and Ferrar et al (2013) 11 described in detail the treatment process of a brine treatment facility in western Pennsylvania, the Josephine Brine Treatment Facility, that exclusively treats oil and gas wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 Ferrar et al (2013) 11 showed that treatment of wastewater by three of these facilities releases elevated concentrations of Cl, Br, Sr, and Ba to streams at concentrations above U.S. Environmental Protection Agency (USEPA) maximum contaminant levels, secondary maximum contaminant levels, criterion maximum concentrations, or criterion chronic concentrations. 11 The disposal of Marcellus wastewater through treatment facilities was also suggested to be linked to an overall increase of 5% in chloride concentrations at downstream surface water monitoring sites in western Pennsylvania 12 and likely increased the salt intake at downstream water treatment facilities. 6,13 Veil (2010) 10 and Ferrar et al (2013) 11 described in detail the treatment process of a brine treatment facility in western Pennsylvania, the Josephine Brine Treatment Facility, that exclusively treats oil and gas wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Drilling in shale formations has varied consequences, creating jobs while also affecting residential property values and human health (Weber 2012;Hill 2013;Olmstead et al 2013;Weber 2013;Brown 2014;Gopalakrishnan and Klaiber 2014).…”
mentioning
confidence: 99%
“…Indeed, the whole process of dealing with fracking's waste water is a highly risky business for local populations and the environment, with considerable risks of water or soil contamination from surface leaks and spills. 101 But perhaps the most concerning issue with waste water is that it can contain significant amounts of radioactive material 102 due to the 'naturally occurring hypersaline brines associated with the formations targeted for natural gas production'. 103 For instance, radium has been found to be building up in rivers downstream of shale gas waste discharge points in Pennsylvania, 104 while a company has been fined for contaminating an aquifer with CBM (termed coal seam gas (CSG) in Australia) waste containing uranium in New South Wales, Australia.…”
Section: Watermentioning
confidence: 99%